Adherence to Life’s Essential 8 enhances gut microbiota diversity and cognitive performance - Wadop, Yannick N.; Muhammad, Jazmyn; Bernal, Rebecca; Satizabal, Claudia L.; Beiser, Alexa; Vasan, Ramachandran S.; Xavier, Ramnik; Kautz, Tiffany; Seshadri, Sudha; Himali, Jayandra Jung; Fongang, Bernard (Frontiers in Microbiomes, 2025)
IntroductionEmerging evidence suggests a complex interplay among cardiovascular health, gut microbiome composition, and cognitive function. Life’s Essential 8 (LE8), developed by the American Heart Association, includes vital metrics of cardiovascular health, such as diet, physical activity, nicotine exposure, sleep health, body mass index (BMI), blood glucose, blood lipids, and blood pressure. MethodsIn this study, we analyzed data from 781 participants in the Framingham Heart Study (FHS) to explore the relationship between LE8 adherence, gut microbiota, and cognitive performance. Multivariable linear regression models and mediation analysis were used to investigate this relationship.ResultsParticipants with greater adherence to LE8 demonstrated significantly increased gut microbial diversity (α-diversity: Chao1, p = 0.0014; Shannon, p = 0.0071) and distinct microbial compositions (β-diversity: PERMANOVA p = 1e-4). Higher adherence to LE8 was related to an increased abundance of genera Barnesiella and Ruminococcus, while a reduced abundance of Clostridium was associated with higher LE8 adherence. Greater gut microbial diversity (α-diversity: Chao1, p = 0.0012; Shannon, p = 0.0066), and beneficial genera like Oscillospira correlated with better global cognitive scores (GCS). Taxonomic overlap analyses revealed microbial taxa that simultaneously influence both LE8 adherence and cognitive outcomes. Mediation analyses indicated that specific taxa, including Barnesiella and Lentisphaerae, mediated the link between LE8 adherence and cognitive performance. These taxa may serve as key modulators in the gut–brain axis, connecting cardiovascular and brain health. Conversely, higher Clostridium abundance was associated with poorer cognitive performance. DiscussionThis study highlights the significance of comprehensive cardiovascular health metrics in shaping gut microbiota and enhancing cognitive resilience. Our findings underscore the therapeutic potential of targeting gut microbiota to mitigate cognitive decline, warranting further exploration through longitudinal and metagenomic studies.